“Opus oratorium”. Between rhetoric and acting in the Middle Ages - Bering, Piotr (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2015)
The following article deals with a possibility of finding some parallels between oratory art and staging. They are often hidden in a text structure, but also an old practice allows us to point many similarities between both arts. Some ancient, medieval treatises were chosen for the further analysis.